Dataset of experimental and computational characterization of tissue spheroid fusion - Steven Ongenae (19646189) (2025)
Collection of hdf5 data files corresponding to the data presented in the original paper (shown by the directory structure). This contains both experimental data (live imaging of spheroid fusion using bright-field and confocal microscopy imaging) and computational data (simulations of active foam using Mpacts). Raw data is not presented, but processed, containing the quantities and metrics reported in the paper. Various csv and xlsx files are attached, which can be readily imported using pandas in Python, relating to: - processed experimental fusion data (100 cells, 500 cells, and new JASP experiments) - measures of granularity / contact angles using GSI - MSRD data from two-photon microscopy experiments - Combined data of all parameter studies and their extracted metrics from the computational model. Furthermore, pickle files of extracted cell tracks are also included.